THE REASONABLE EXPLANATION OF ANNIHILATION (FANÄ€) IN MYSTICISM - shamshaki, Abul-Fadli Kia (Sekolah Tinggi Filsafat Islam (STFI) Sadra, 2012)
Mystics are passing through stages (degrees of mystic perfection) and esoteric abodes (spiritual stations) in their spiritual journey to Allah which is difficult for unmystics to understand. Because of this, most of the reflective people are trying to rely on their intellectual and theoretical principles to obtain an understandable explanation of mystical experiences and ecstasy. However the success of such explanation completely lies in the power and strength of the above mentioned principles. (FanÄ) or annihilation is one of the mystical stages or states which unmystics find very difficult to reasonably understand, hence various and different theories have been provided for its explanation. Various scientific and philosophical achievements are appropriate explanations of annihilation (fanÄ) which is valuable in its place; however effort had been made in this article to prove that the only successful explanation is an explanation based on the principles of transcendental theosophy and theoretical mysticism